Program KKN Tematik: Sosialisasi Pemuda Berkarakter, Agen Perubahan, Dan Anti-Korupsi Bersama Civitas AMGPM - Sherynzwing Margareth Tuahatu; Frisca Claudia Tumury; Stivano Joris (CV. Multi Kreasi Media, 2024)
Real Work Lectures (KKN) are a form of community service carried out by students as part of academic activities at Indonesian universities, especially in the aspect of human resource development. This aims to form a young generation with integrity, responsibility and a high awareness of the values ​​of honesty and transparency. One of the programs implemented is